(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Uzbekistan in 1991 to independence after reaching, education the system is also large to changes face came. In particular, the general middle education — that is elementary and of the school middle stage — this period inside structure in terms of, content in terms of and infrastructure in terms of noticeable updates in this article, the years 1991-2025 between general middle education in the field was main changes seeing is released.